Electrochemical Modulation of the Fluorescence of Cyanine Dye Cy5. Issue 8 (11th May 2015) - Zhang, Min; Jiang, Junguang; Cai, Mingjun; Wang, Hongda
Abstract Organic fluorescent dyes are widely used in single molecule localization microscopy, where their performances are determined by the photophysical properties. Herein, we utilized a sensitive method to modulate the fluorescence of organic dyes by external potentials using a combination of electrochemical cell and super‐resolution fluorescent microscopy. Cy5 (cyanine dye) was chosen as a model molecule considering its wide application and commercial availability. We applied different potentials on the Au electrode to change the Coulombic charge microenvironment of Cy5. When the electrode potential was adjusted negatively, Cy5 displayed a better photostability. This method is proved effective in adjusting the fluorescence of organic dyes.